Strategi Pengembangan Ekonomi Lokal Kabupaten Gianyar: Pendekatan Analisis Shift-share, Location Quotient, dan SWOT - Juytha Friani Sitio; Km Putri Tristiari Sutaryantha; Triska Rosari Ada'; Nurcahyaningtyas Subandi (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2025)
This research aims to identify and analyze sectors of the local economy in Gianyar Regency, Bali, using Shift-Share, Location Quotient, and SWOT analysis approaches. The methodology employed includes secondary data collection and statistical analysis to determine the sectors with the highest development potential. Findings indicate that tourism, health services, and mining are the most promising sectors for development. Additionally, the SWOT analysis identifies challenges such as high competition with other regions and the need for optimal licensing. The contributions of this research provide insights for better and sustainable local economic development planning in Gianyar Regency, as well as practical implications for policymakers and business actors in the region.